Determinant of online shopping intention: Satisfaction as an intermediary - Sukesi, Sukesi (Journal of Innovation in Business and Economics, 2023)
Conducted with a sample size of 120, the research employed structural equation modeling for analysis. The findings revealed several influential factors, including perceived trust, perceived value, perceived risk, and satisfaction, impacting behavioral intentions among Indonesian online shoppers. Notably, satisfaction emerged as a mediating variable in the relationship between perceived trust, perceived value, perceived risk, and behavioral intentions. The implications suggest that businesses and online retailers seeking to enhance customer satisfaction and drive desired behaviors should consider strategies aligned with these influential factors. However, it is crucial for both researchers and practitioners to acknowledge the study's limitations. Further research endeavors are encouraged to broaden and refine our understanding of consumer behavior in the Indonesian online shopping landscape.